What Do Transgender Women’s Experiences Tell Us about Law? Towards an Understanding of Law as Legal Complex - Esen Ezgi Tascioglu (Oñati Socio-Legal Series)
Based on ethnographic study conducted in Istanbul, this thesis investigates the effects of law and legal operations on transgender women’s sex work and daily lives, and seeks to disentangle the multidimensional ways through which they and their conduct are governmentalized by law in Turkey. The first part of the thesis discusses the legal dynamics surrounding transgender sex work and delineates how transgender women are expulsed from regulated sex work by the interaction of the socially produced desire around their bodies and law. Led to work outside the regulated sex trade, transgender women navigate spaces which are regulated in an ambivalent manner yet which have the net effect of drawing transgender women into street sex work. The second part shows that these legal practices on sex work do not apply to all sex workers but to nearly all transgender women, depriving them from their most basic rights. Overall my analysis demonstrates that transgender women find themselves in a multitude of legal and institutional practices that are borne out of the interaction of their social contexts, their bodily performances and legal texts and their application, and that this is done through various regulatory agents. I argue that such an examination demonstrates law’s multiplicity and heterogeneity against the unitary and sovereigntist understandings of law which prevail in popular discourse as well as scholarly and activist thinking in Turkey and abroad.